2012
DOI: 10.1017/s0143385711001003
|View full text |Cite
|
Sign up to set email alerts
|

On recurrence and ergodicity for geodesic flows on non-compact periodic polygonal surfaces

Abstract: International audienceWe study billiard dynamics on non-compact polygonal surfaces with a free, cocompact action of Z or Z(2). In the Z-periodic case, we establish criteria for conservativity. In the Z(2)-periodic case, we study a particular family of such surfaces, the rectangular Lorenz gas. Assuming that the obstacles are sufficiently small, we obtain the ergodic decomposition of directional billiards for a finite but asymptotically dense set of directions. This is based on our study of ergodicity for Z(d)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…The cocycles that arise in this setting are piecewise constant functions with values in Z d . First results in these geometric settings were only recently proved in [6,14,15,17,18].…”
Section: T ϕ (X Y) = (T X Y + ϕ(X))mentioning
confidence: 99%
See 1 more Smart Citation
“…The cocycles that arise in this setting are piecewise constant functions with values in Z d . First results in these geometric settings were only recently proved in [6,14,15,17,18].…”
Section: T ϕ (X Y) = (T X Y + ϕ(X))mentioning
confidence: 99%
“…We present here below a particular variation on the construction of Katok, using Rauzy-Veech induction (Definition 5.1), which allows us to obtain further properties (in particular Lemma 5.3) needed in the following sections. 6 Notation Let α ∈ A be such that π 0 (α) = 1, i.e. I α is the first of the intervals exchanged by T .…”
Section: Rigidity Sets With Large Oscillations Of Birkhoff Sumsmentioning
confidence: 99%
“…We give below a short description of this model (cf. [CoGu12]) and show that for special directions the previous results on ergodic sums over rotations apply.…”
Section: Description Of the Modelmentioning
confidence: 70%
“…One can reduce the model to the case of a direction of flow with angle η = π/4 and with the small obstacles condition a + b ≤ 1 (see [CoGu12]). Without loss of generality, we will consider this case.…”
Section: Rational Directions and Small Obstaclesmentioning
confidence: 99%
“…If P=[0,a]×[0,b] then the corresponding billiard table we denote by E(Λ,a,b). The recurrence, ergodicity and diffusion times of standard Ehrenfest wind‐tree model, with Λ=Z2, were discussed recently in . In particular, it was recently shown that for every pair of parameters (a,b) and almost every direction θ the billiard flow on E(Z2,a,b) is recurrent and non‐ergodic and its rate of diffusion is t2/3.…”
Section: General Wind‐tree Modelmentioning
confidence: 99%